Structures and Properties of Luminescent Pentanitratoeuropate(III) Ionic Liquids. Issue 3 (16th December 2014) - Zhao, Ying; He, Ling; Tang, Ning; Qin, Song; Tao, Guo‐Hong; Liang, Fu‐Xin
Abstract: A series of luminescent ionic liquids based on pentanitratoeuropate(III) anions combined with imidazolium cations, namely, 1, 2, 3‐trimethylimidazolium [MC1 mim]2 [Eu(NO3 )5 ] (1), 1, 3‐dimethylimidazolium [C1 mim]2 [Eu(NO3 )5 ] (2), 1‐ethyl‐3‐methylimidazolium [C2 mim]2 [Eu(NO3 )5 ] (3), 1‐butyl‐3‐methylimdazolium [C4 mim]2 [Eu(NO3 )5 ] (4), 1‐hexyl‐3‐methylimidazolium [C6 mim]2 [Eu(NO3 )5 ] (5), and 1‐methyl‐3‐octylimidazolium [C8 mim]2 [Eu(NO3 )5 ] (6), were synthesized. These complexes were characterized by NMR and IR spectroscopy as well as elemental analysis. They exhibit high thermostability and wide liquidus ranges of more than 300 °C. Colorless plate crystals of 1 were isolated, and the crystal structure was determined by single‐crystal X‐ray diffraction [monoclinic system, C 2/ c space group with the cell parameters a = 21.6870(6) Å, b = 9.9807(4) Å, c = 15.0267(6) Å, β = 131.140(4)°, Z = 4]. In the [Eu(NO3 )5 ] 2– anion, the 10‐coordinate Eu III ion is coordinated by five bidentate nitrate ligands and has a highly symmetrical trigonal‐bipyramidal geometry. Compounds 1–6 exhibit bright red luminescence of high colorimetric purity. Only two characteristic narrow monochromatic bands, arising from the 5 D0 → 7 F J ( J = 1 and 2) intraconfigurational f–f transitions, were clearly observed in their emission spectra at 298 K. The intense red photoluminescence is still stable at 150 °C. These 10‐coordinated Eu III complexes are of interest as potential thermally stable luminescent soft materials. Abstract : A series of luminescent ionic liquids based on pentanitratoeuropate (III) anions are synthesized and characterized. These complexes exhibit high thermostability and a wide liquidus range. The 10‐coordinate [Eu(NO3 )5 ] 2– anion has a highly symmetric trigonal‐bipyramidal structure. Complexes1 –6 exhibit bright red luminescence with narrow‐band and intense emission of high colorimetric purity.